School performance and the risk of suicide attempts in young adults: a longitudinal population-based study. Issue 6 (24th July 2013) - Kosidou, K.; Dalman, C.; Fredlund, P.; Lee, B. K.; Galanti, R.; Isacsson, G.; Magnusson, C.
Abstract : Background: Poor school performance is strongly associated with attempted suicide, but the mechanisms underlying this association are uncertain. We examined this relationship and the extent to which it is explained by (i) adult health behaviours and (ii) social conditions. Furthermore, we examined the potential modifying role of previous suicidal thoughts in the relationship. Method: We conducted a longitudinal cohort study of 6146 individuals aged 18–33 years, recruited in 2002 and 2006 in Stockholm and resurveyed in 2007 and 2010 respectively. We estimated the risk of reported lifetime suicide attempts at follow-up among individuals without a history of suicide attempts at baseline and in relation to compulsory school-leaving grades, controlling for possible confounders and mediators. Results: There were 91 cases of self-reported suicide attempts during the follow-up (5-year incidence of 1.5%). ORs ranged from 3.35 [95% confidence interval (CI) 1.88–5.96] for those in the lowest grade quartile to 2.60 (95% CI 1.48–4.57) and 1.76 (95% CI 0.99–3.13) for those in the second and third quartiles respectively. The relationship between school performance and risk of suicide attempts did not differ by sex. Adult health behaviours and social conditions marginally attenuated, but did not explain, the relationship. The gradient varied with baseline history of suicidal thoughts, and was found only among individuals without such a history. Conclusions: Poor school performance was found to predict suicide attempts among young adults without a history of suicidal thoughts. Adult health behaviours and social conditions did not explain this relationship. Instead, other factors linked with poor school performance, such as poor coping ability, may increase the risk of suicide attempts.